J05 Development and characterisation of the cognitive assessment battery (CAB-HD) for Huntington's disease clinical trials. (29th August 2012) - Stout, J; Queller, S; Baker, K; Borowsky, B
Abstract : Background: Decades of research confirm that cognitive function declines in the premanifest and early stages of Huntington's disease (HD). Therapeutic agents designed to improve cognitive function in HD are currently in development. Thus, there is a need to develop reliable and practical cognitive tools that can provide evidence of both impairment in HD and improvement in the context of a clinical trial. Aims: The CAB-HD project aims to capitalise on findings from previous studies to create and characterise a set of cognitive measures that can be applied in upcoming clinical trials to assess cognition in HD. Measures evaluated include core cognitive tests with extant evidence of impaired performance and progressive decline in premanifest or early HD, as well as several provisional cognitive tests that have been less studied in HD to date. Methods: The CAB-HD study examined 250 participants (100 controls, 100 late premanifest, 50 early HD) from English-speaking sites in Australia, the US, Canada, and the UK, using a set of 14 cognitive tests that were repeated at each of three time points (two consecutive days and 6 weeks later). Results: In addition to validating prior research indicating that these cognitive tests show worse performance in CAG expanded subjects as compared to control subjects, the data are being analysed to determine (1) test-retest reliability over periods relevant to clinical trials, (2) optimal ways to use alternate forms or test pre-exposure to manage practice-related effects on test performance, (3) ability of a composite cognitive score to improve the sensitivity or reliability over that of individual test scores, and, (4) feasibility and tolerability of the testing battery. Conclusions: The CAB-HD study has met recruitment goals and cognitive batteries that are both scientifically justified and pragmatically feasible in the context of HD clinical trials will be proposed.